UNCOMMON CAUSE OF SECONDARY EMPTY SELLA SYNDROME - Affendi, Sharifah Noor Adrilla Long Mohd Noor; Ma’arof, Mohd Sofi Hafizi Sarip @; Adam, Noor Lita; Karim, Nor Afidah (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic has led to detrimental outcomes worldwide, leading to millions of deaths. SARS-CoV-2 vaccines are a critical step for many countries in battling with this infection. Recently, there are increasing cases of endocrinopathy, including hypophysitis, associated with SARS-CoV-2 vaccination. CASE We describe a patient with hypophysitis as a sequalae of COVID-19 vaccination. A 48-year-old male, with a history of pulmonary tuberculosis who completed treatment in 2016, presented with fever, chills, postural hypotension and left upper limb weakness. The symptoms appeared 2 weeks after his 1st dose of SARS-CoV-2 vaccination. He was initially treated as acute disseminated encephalomyelitis (ADEM) and meningoencephalitis. During admission, he developed septic shock with multiorgan involvement. He remained hypotensive despite improvement of septic parameters. Hence, short synacthen test was done which revealed inadequate cortisol response. Inpatient cerebrospinal fluid (CSF) investigations were normal. Cranial MRI showed asymmetrical white matter hyperdensities; possible aetiology included infectious and inflammatory causes. He was discharged well with oral hydrocortisone 10 mg bd. Evaluation in an endocrine clinic showed that he had low cortisol with low ACTH levels. Moreover, insulin tolerance test done confirms inadequate ACTH and growth hormone response. Other anterior hormonal profile results were normal. In view of the evidence of hypothalamic-pituitaryadrenal (HPA) axis suppression, coupled with the pituitary MRI findings, the diagnosis of SARS-CoV-2 vaccinationinduced hypophysitis was established. CONCLUSION SARS-CoV-2 vaccination-induced hypophysitis is a rare but significant adverse effect that needs to be recognised. Prompt diagnosis is crucial, as treatment with steroid is lifesaving. In light of our experience, diagnosis of hypophysitis should be considered when patients present with pituitary dysfunction with a history of recent COVID-19 vaccination.